Application of cash waqf in the empowerment of widows in Malaysia - Amuda, Yusuff Jelili; Abdul Razak, Dzuljastri; Ahmedhas, Aminath Amany (Journal of Advanced Management Science, 2016)
Cash Waqf is a form of Islamic endowment that has enormous un-utilized potential for its application in fulfilling the unmet social needs of the community. One such need is for the establishment of more effective schemes to alleviate the struggles faced by widowed women such as poverty, unemployment, and lack of support. The objective of this paper is to examine how Cash Waqf can be channeled into various mediums, instruments, and projects that will assist in empowerment and improvement of needy widows and their dependent children. The research uses a qualitative approach to examine the applicability of Cash Waqf funds for this purpose and presents a case for innovative avenues through which Waqf funds can be effectively mobilized towards this end. The paper proposes strategies through which Cash Waqf can be used for the creation of resources and tools for empowerment of widowed women such as through educational funds, creation of employment opportunities, and provision of tools for entrepreneurial activities.